2017
DOI: 10.1038/s41598-017-14212-3
|View full text |Cite
|
Sign up to set email alerts
|

Cooling combined with hyperoxic CO2 anesthesia is effective in improving the air exposure duration of tilapia

Abstract: Tilapia were subjected to cooling (CO, a stepwise reduction in temperature from 30 °C to 15 °C), anesthesia (AN, anesthetized by hyperoxic carbon dioxide), air exposure (AE, exposed to air) and cold tolerance (CT, in 15 °C water) treatments, and the physiological responses were determined after the treatments. CO followed by AN treatment for tilapia could meet the criteria of an ideal anesthetic. Fish were deeply sedated within 69 s, completely anesthetized within 276 s and recovered within 308 s without any m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The increase in RBC directly induced an elevation in HCT. The stress response did not disappear immediately after the fish recovered, consistent with the prior observations of strong stress responses in fish 30 min after recovery, with the subsequent return to basal values of stress response indicators, such as HCT and cortisol, within 90 min [ 14 , 26 ]. However, the changes in MCH before and during hibernation and after recovery were not significantly different, indicating that the combined method of hypothermia hibernation and CO 2 anesthesia for the large yellow croaker did not influence the hemoglobin transport function.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The increase in RBC directly induced an elevation in HCT. The stress response did not disappear immediately after the fish recovered, consistent with the prior observations of strong stress responses in fish 30 min after recovery, with the subsequent return to basal values of stress response indicators, such as HCT and cortisol, within 90 min [ 14 , 26 ]. However, the changes in MCH before and during hibernation and after recovery were not significantly different, indicating that the combined method of hypothermia hibernation and CO 2 anesthesia for the large yellow croaker did not influence the hemoglobin transport function.…”
Section: Resultssupporting
confidence: 86%
“…This rapidly decreased to 58.33% for 2.5 h when the aeration rate increased to 7.0 ppm/s. This may be because the rapid increase in CO 2 concentrations inhibited the loading of oxygen on red blood cells, resulting in hypoxic respiratory failure [ 10 , 14 ]. Our results suggested that the aeration rate of CO 2 at 2.0 ppm/s was the optimal anesthesia condition for the large yellow croaker.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations